2011
DOI: 10.1038/ijo.2011.138
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a continuous metabolic syndrome score in Indian children for detecting subclinical atherosclerotic risk

Abstract: Objective: To evaluate the continuous metabolic syndrome score (cMetS) in Indian children and to investigate its relationship with the risk of carotid arterial stiffness. Methods: Data on weight, height, mean arterial pressure, serum lipids, insulin, glucose, carotid intima-media thickness and stiffness parameters, that is, pulse wave velocity (PWV), elasticity modulus (Ep), stiffness index (b) and arterial compliance (AC), were assessed in 236 children (6-17 years) from Pune city, India. cMetS was computed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 28 publications
2
43
0
3
Order By: Relevance
“…A study in Indian children investigating the association between cMetS and risk of carotid arterial stiffness, found a graded relationship between cMetS and risk factors of MetS, and that children with higher cMetS had higher risk of carotid arterial stiffness than those with lower cMetS [54]. Due to the limited data available on the cMetS in adolescence, to the best of our knowledge, this is the first study to demonstrate that cMetS and its components are associated with impairment of CAM, even in apparently healthy adolescents without symptomatic metabolic abnormalities or clinically abnormal cMetS components.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Indian children investigating the association between cMetS and risk of carotid arterial stiffness, found a graded relationship between cMetS and risk factors of MetS, and that children with higher cMetS had higher risk of carotid arterial stiffness than those with lower cMetS [54]. Due to the limited data available on the cMetS in adolescence, to the best of our knowledge, this is the first study to demonstrate that cMetS and its components are associated with impairment of CAM, even in apparently healthy adolescents without symptomatic metabolic abnormalities or clinically abnormal cMetS components.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,20 One previous study demonstrated a correlation between PWV and continuous metabolic syndrome score in Indian children. 21 This evidence suggests that obesity may be an independent factor affecting the status of the vascular wall. However, this association is likely diseasestage specific, as it was shown to be particularly strong in adult patients with angiographic evidence of changes in coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai titik potong didefi niskan sebagai nilai antara normal dan abnormal atau nilai batas hasil uji positif dan negatif (10). Di beberapa negara sudah memiliki titik potong skor sindroma metabolik seperti di India, Iran, dan Brazil (11)(12)(13). Indonesia belum memiliki nilai titik potong skor sindroma metabolik khususnya pada remaja sehingga diperlukan penelitian terkait penentuan nilai titik potong skor sindroma metabolik di Indonesia.…”
Section: Who); National Cholesterol Education Program Expert Panel Onunclassified